2012
DOI: 10.1177/1049732312469463
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the Aftershock

Abstract: In this research we examined how the conditions of Haiti's tent communities, inhabited by those displaced by the January 10, 2010, earthquake, shaped access and adherence to highly active antiretroviral treatment (HAART) for Haitians with HIV. Conditions in the encampments were marked by unhygienic and cramped living spaces, exposure to the elements, a lack of privacy, unavailability of food and clean water, and a dependence on poorly functioning aid agencies. These conditions shaped access and adherence to HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Prior to the earthquake, Haiti had the highest rate of PLWH in the Caribbean with an estimated 120,000 PLWH (9). A number of researchers have begun to document the immediate structural and psychological effect of the earthquake on Haitians living with HIV/AIDS, including on substance use, access and adherence to treatment, however the long term effects of the earthquake on the country’s HIV/AIDS trajectory may not be fully understood for many years (1014). …”
Section: Introductionmentioning
confidence: 99%
“…Prior to the earthquake, Haiti had the highest rate of PLWH in the Caribbean with an estimated 120,000 PLWH (9). A number of researchers have begun to document the immediate structural and psychological effect of the earthquake on Haitians living with HIV/AIDS, including on substance use, access and adherence to treatment, however the long term effects of the earthquake on the country’s HIV/AIDS trajectory may not be fully understood for many years (1014). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated populations that may be at greater risk of health inequalities 19 including those with physical disability [20][21][22] , HIV [23][24][25][26][27][28][29][30][31][32][33] , mental illness 15,[34][35][36] socioeconomic deprivation 14,[37][38][39] , refuge or displacement 13,25,37,[40][41][42] , opioid or other substance misuse or dependence 30,[43][44][45][46] , people of black and minority ethnicity 38,43,47 and men who have sex with men 31,48 .…”
Section: Rq3 Public Health Emergency and Participant Characteristics ...mentioning
confidence: 99%
“…A quantitative outcome of "adherence" or "compliance", as termed by the study authors, was reported in 30 studies, using four distinct measurement types: (1) A discrete self-report at one time point using a variety of phrasing of questions (n=24) 24,25,32,33,36,53,56,61,[68][69][70][71][72][73][74][75][76][77][78][79] , (2) a discrete single time point measure comparing two study groups 54,57,80 , (3) discrete measures at two times points 16,23,[81][82][83] and (4) calculated based on days of tablets remaining 28 .…”
Section: Rq4 Study Outcomes Measuredmentioning
confidence: 99%
“…This has been reported among internally displaced people in Haiti. 19 Self care interventions could offer confidential and accessible information for this important group. For example, tailored information could be shared on mobile phone apps.…”
Section: Intersectional Identities Among Marginalised Forcibly Displamentioning
confidence: 99%